Information Technology - Tool to Deal with Bullwhip Effect in Supply Chain Management - Gupta, Sachin; Mishra, Pranav (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Over the past decade, the traditional purchasing and logistics functions have evolved into a broader strategic approach to materials and distribution management known as supply chain management. This research reviews the literature base and develops the effectiveness of supply chain management using the modern practices of information technology. This research also discusses various supply chain management strategies that require complex decision making form time to time and to deal with variety of situations and huge amount of data. The use of modern information technology becomes an indispensable tool for designing and managing complex supply chain systems. In present research the implementation of management information system has also been explored.